Discovering biomarkers of postharvest resilience and flavour life in imported citrus and table grapes. - Navarro-Calderon, Angela (Cranfield University, 2022)
Clementines and table grapes, which are the main fruit crops consumed in the UK after bananas and apples, are considered non-climacteric fruit, not showing an increase in respiration rate and ethylene production during ripening. Previous research has suggested that a different ripening hormone, abscisic acid (ABA), has a more crucial role in the ripening of this kind of produce. The study presented herein aimed to identify biomarkers of postharvest resilience and flavour life of imported clementines and table grapes. For these studies two experiments were designed with the common objectives of determining: 1) the pre- or postharvest factors influencing the postharvest produce quality – both physiological and biochemical, and 2) the role of ABA and ABA catabolites on fruit senescence. The main findings from these studies were that the canopy position of clementines significantly affected fruit postharvest quality and hormonal content. Fruit located on the inside canopy showed higher RR and lower sugar content than outside fruit at the end of postharvest storage, resulting in a shorter shelf- life. At the same time, inside fruit showed a higher content of ABA and ABA catabolites than outside fruit, coinciding with a lower consumer preference score for external appearance, aroma and flavour. This is the first study that determined the ABA and ABA catabolite contents in the pulp of clementines from different canopy positions during senescence, and related this to consumer acceptance. The use of an ethylene inhibitor, 1-methylcyclopropane (1-MCP), during the postharvest storage of table grapes was investigated. The treatment did not have a positive effect on their postharvest quality; in fact, grapes were significantly affected by mould incidence at the end of the shelf-life. The hormonal content in different berry sections was also evaluated; the distal section, which showed a higher mould incidence than the proximal, had three times more ABA and ABA catabolites than the proximal section. This is the first time that the spatial distribution of ABA during the senescence of table grapes was profiled. Despite being different products, similar novel results were observed for both clementines and table grapes. This study indicated that senescence processes in these non-climacteric produce was initiated after a significant increase in RR, and that ABA could be considered a biomarker for clementines and table grapes senescence since an ABA peak during postharvest storage preceded an increase in RR, mould incidence, organic acids, and sucrose hydrolysis. This coincided with a decrease in berry firmness. These findings are of significant importance for the industry. Understanding how ABA regulates senescence processes and the quality changes taking place during postharvest cold storage of clementines and tables grapes improves the consistency in fruit quality and reduces waste and consumer complaints. Although clear beneficial findings have been identified, the results of this study were limited by time, resources, climatic conditions, and other factors. Therefore, recommendations for future work are: to perform molecular studies on genes regulating the ABA pathway from field to postharvest storage; to investigate the crosstalk between ABA, ethylene, and sucrose from ripening to senescence; and to further investigate the use of shade nets and harvesting by canopy position on fruit quality consistency and consumer acceptance.
Keywords: senescence; abscisic acid; ethylene; 1-methylcyclopropane; canopy; postharvest; clemetines; table grapes; consumer; fresh produce supply chain